Effects of temperature and novobiocin on the expression of calf prochymosin gene and on plasmid copy number in recombinant Escherichia coli - Kaprálek, F; Tichý, P J; Fábry, M; Sedlácek, J (Folia microbiologica, 1998)
Escherichia coli strain HB101 harboring an expression plasmid bearing calf prochymosin gene under the control of the tac promoter was grown in the presence of IPTG with or without novobiocin at 28 and 40 degrees C, respectively. The differential rates of synthesis of prochymosin inclusions, and, for comparison, of beta-lactamase and beta-galactosidase, as well as plasmid copy number, were determined during the first hours of steady state growth. At 28 degrees C the induced expression of prochymosin gene was almost blocked. Addition of novobiocin did not alleviate this effect. In fact, it strengthened it, and we conclude that both these additive inhibitory effects are a consequence of the decrease in negative superhelical tension of plasmid DNA to an insufficient level. At 40 degrees C the differential rate of prochymosin synthesis was markedly enhanced. Since the copy number of the expression plasmid increased approximately to the same extent, we conclude that an increase in gene dose is the cause. The stimulation of cloned heterologous gene expression at 40 degrees C and inhibition at 28 degrees C may be conveniently used in biotechnological-scale cultivations of some recombinant bacteria.
Keywords: exprese genu; Gene Expression; prekurzory enzymů; vysoká teplota; Hot Temperature; chymosin; genová dávka; Novobiocin; Escherichia coli; Recombinant Proteins; plazmidy; zvířata; rekombinantní proteiny; Cattle; superhelikální DNA; skot; Topoisomerase II Inhibitors; Animals; novobiocin; Plasmids; DNA, Superhelical; inhibitory topoisomerasy II; Chymosin; Gene Dosage; Enzyme Precursors